The Effect of Different Freezing Rates and Long-Term Storage Temperatures on the Stability of Sliced Peaches - Paul Dawson; Wesam Al-Jeddawi; James Rieck (International Journal of Food Science)
The purpose of this research was to determine if freezing rates and holding temperatures influence peach quality during short- and long-term frozen storage. Fresh peaches (Prunus persica) were purchased locally, sliced, dipped in 2% ascorbic acid then drained, and packaged. The study was divided into two experiments, one to determine the effect of the freezing rate on peach quality and the second to determine the effect of frozen holding temperatures on peach quality. For the freezing rate experiment, freshly packaged peaches were placed in freezers at different temperatures (-7°C, -12°C, -18°C, -29°C, and -77°C) then removed for testing when the core temperature of the peaches reached the temperature of all freezer temperatures. The second experiment determined the long-term holding effect on quality using both fresh and prefrozen peaches held at -7°C, -12°C, -18°C, -29°C, and -77°C through 360 days. Quality measurements included freeze thaw and weight loss, lightness, firmness, moisture content, ascorbic acid equivalent antioxidant capacity (AAEAC), hexanal detection using gas chromatography (GC), scanning electron microscopy (SEM), and sensory evaluation. During the freezing phase (experiment 1), peach weight loss and surface ice crystal pore size significantly decreased with increased freezing rates. Peaches held at -77°C and -29°C maintained overall quality to a greater degree than the higher holding temperatures. However, all samples enzymatically browned when thawed; therefore, frozen peaches may best if used in the frozen state or in applications where appearance is a critical factor. In general, fresh and prefrozen peaches were not acceptable by the sensory panelists after 270 days of frozen storage.